EFEK HEPATOTOKSIK ANTI TUBERKULOSIS TERHADAP KADAR ASPARTATE AMINOTRANSFERASE DAN ALANINE AMINOTRANSFERASE SERUM PENDERITA TUBERKULOSIS PARU - Delita Prihatni; Ida Parwati; Idaningroem Sjahid; Coriejati Rita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Tuberculosis (TB) is still a major health problem, especially in the developing countries. The combination of antituberculosis drugs are generally recommended for the treatment of tuberculosis. Van Crevel study in Jakarta found that most (70%) of patients with pulmonary TB who received combined antituberculosis drugs with standard (450 mg) dose rifampicin had very low plasma rifampicin level. Based on this results, TB Research and Clinical Trial Centre Bandung & University Medical Centre Nijmegen, The Netherlands conduct the study which compared clinical outcome between standard and high (600 mg) dose of rifampicin. Most of antituberculosis drugs currently available are very low in causing acute and chronic toxicities, however we must keep aware of side effect during the treatment. The most serious adverse effect of several drugs is liver damage (drug induced hepatitis) and potentially fatal hepatitis. To detect liver demage earlier aspartate aminotransferase( AST) and alanine aminotransferase (ALT) serum level were examined during antituberculosis treatment. The aim of this study was to determine AST and ALT serum level at intensif phase of antituberculosis treatment with standard and high dose rifampicin. The study had been done from August 2003 to September 2004 at Dr Hasan Sadikin Hospital and Balai Pengobatan Penyakit Paruparu, Bandung. The subjects were divided randomly into 2 groups. The first group consisted of patients with category I antituberculosis drugs with standard dose rifampicin and the second group patients also category I with high dose rifampicin. Aspartate aminotransferase and ALT serum level were examined at week 0 (before treatment), 2nd, 4th, and 8th. This was randomized clinical trial with paralel design study. Statistical analysis used paired t test to compare the dose effect of rifampicin to AST and ALT serum level changes, t independent test to compared mean difference of AST and ALT serum level changes which is projected by profile analysis. p value < 5%.. The prevalence of the hepatotoxicity were 17.39% of standard dose and 18.17% of high dose rifampicin. The hepatotoxicity were mild and moderate level,and it was already present at 2 weeks of therapy. There were no significant difference of AST and ALT serum level beetween those two groups. Conclusion: In this study antituberculosis drugs with high dose rifampicin were safe for TB patients.